2020
DOI: 10.1186/s12889-020-08506-x
|View full text |Cite
|
Sign up to set email alerts
|

“What will my child think of me if he hears I gave him HIV?”: a sequential, explanatory, mixed-methods approach on the predictors and experience of caregivers on disclosure of HIV status to infected children in Gombe, Northeast Nigeria

Abstract: Background: With increasing access to effective Anti-Retroviral Therapy (ART), the proportion of children who survive into later childhood with HIV has increased. Consequently, caregivers are constantly being confronted with the dilemma of 'if', 'when', and 'how' to tell their children living with HIV their status. We aimed to determine the prevalence and predictors of disclosure and explore the barriers caregivers face in disclosing HIV status to children living with HIV in Gombe, northeast Nigeria. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…The fear of being blamed, the fear that the child will not maintain the secrecy of the HIV status, and the fear of subsequent stigma and negative discrimination against the entire family largely influenced the timing of the disclosure. Other studies conducted with caregivers have reported that the high levels of internalised HIV stigma and shame on the part of biological mothers living with HIV induced them to delay disclosure to their children [ 21 , 42 , 43 , 44 , 45 , 46 ]. Reducing the stigma associated with HIV infection is critical in this setting to create a safer and more supportive environment for the timely and safe disclosure to children [ 11 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fear of being blamed, the fear that the child will not maintain the secrecy of the HIV status, and the fear of subsequent stigma and negative discrimination against the entire family largely influenced the timing of the disclosure. Other studies conducted with caregivers have reported that the high levels of internalised HIV stigma and shame on the part of biological mothers living with HIV induced them to delay disclosure to their children [ 21 , 42 , 43 , 44 , 45 , 46 ]. Reducing the stigma associated with HIV infection is critical in this setting to create a safer and more supportive environment for the timely and safe disclosure to children [ 11 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HCWs believed that mothers fear being considered by their children to have been promiscuous, following the disclosure of their children’s HIV serostatus. Research suggests that caregivers who lack the skill to handle the disclosure process positively opt for silence, in the process delaying disclosure to later in their children’s adolescence [ 7 , 11 , 12 , 22 , 24 , 27 , 29 , 43 , 46 ]. HIV-positive mothers who have not accepted their own status and struggle with coping find it more difficult to disclose the child’s status because of discomfort with the issue of their own HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…The context surrounding the child's right to know about their diagnosis is ensured in official documents that recommend that they receive information about their clinical condition and treatment, respecting their level of understanding (31) . Family members as well as professionals must guarantee this right and be clear about the benefits (7) for the child to know their diagnosis, such as: adherence to treatment, encouragement for self-care and future safe sexual behavior. It is essential to prevent them from reaching adolescence without knowing the diagnosis (2) .…”
Section: Discussionmentioning
confidence: 99%
“…A study with 120 primary caregivers of Nigerian children aged 6 to 17 years old indicated that the disclosure of an HIV diagnosis can foster health benefits for these children (7) . A systematic review indicated that full disclosure ranged from 1.7% to 41.0%, and 49.5% of children received information that was deflected to explain the illness and health appointments (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Mothers worry about the shame of being seen as the source of the infection and subsequently being blamed by the children. 10,16,36,44,45 This explains why mothers lie or use deflective disclosure in their discussion about the source of their children’s infection. There is a need for HCWs to prepare and support caregivers to develop appropriate responses to children’s questions about the source of infection instead of deflecting the questions.…”
Section: Discussionmentioning
confidence: 99%